Immobilisation and characterisation of chlorella vulgaris as potential bio-indicator for selected herbicides - Desa, Shakinaz (2001)
Herbicides are one of the major contributing pollutants in water bodies. Several detection methods have been developed to monitor herbicide pollution including the use of bio-indicators. The competency of a bio-indicator in herbicide detection must comply with the sensitivity and efficiency of the method. In this study, Chlorella vulgaris as a bioindicator was immobilised in alginate and compared with the free cell to determine its ability as a bio-indicator. There were two immobilised conditions; immobilised cells of recommended cell concentration (2x10⁴cells/ml) and immobilised cells based upon suitability test. In the suitability test, four bead concentrations were tested; 0.1%w/w, 0.2%w/w, 0.4%w/w and 0.8%w/w. 0.1%w/w was selected as test bead based on stability and water and 26 days in calcium chloride. The other bead concentrations were stable for less than 20 days. The 0.1%w/w bead had constant growth rate and exponential rate pattern of oxygen production for 7 days, compared with the other beads. Free cells and two immobilised conditions were compared using two methods; oxygen production rate inhibition test and 96 hour's toxicity test. Four herbicides were used in this study; Atrazine, Simazine, Diuron and Paraquat. The first three are photosystem II inhibitor and Paraquat is a photosystem I inhibitor. Immobilised microalgae was dark incubated in herbicide for 30 minutes before measuring the oxygen production rate. 30 minutes was chosen as incubation time due to significant inhibition of oxygen production rate by herbicide at this period. Light and temperature values during detection were previously examined and selected for suitability. The selected light intensity was 90µmol/sec/m2 and 28°C for sample chamber's temperature due to the production of oxygen at exponential rate. Cells were incubated for 96 hours in herbicide with 12: 12h light cycle for 96 hour's toxicity test. Cells were enumerated and compare to reference. For immobilised cells, cells were counted after dissolving the beads with trisodium citrate. There were three significant findings in this study. First, the ability to immobilise Chlorella vulgaris as a 2mm bead, which can survive for more than three months. Second, immobilisation of the recommended cell number was the better choice as bio-indicator using oxygen production rate change compared to free cells or test bead. There was 50% inhibition using this condition at 0.12µM Atrazine, 5.8µM Simazine, 0.4µM Diuron and calculated value at 3.913 mM for Paraquat, while the other cell conditions needed higher concentration than 1000µM for 50% inhibition or could not exhibit 50% inhibition. Third, for toxicity testing, free cells is recommended compared to the immobilised cells. Toxicity of free cells at 1000µM was higher in Simazine > Atrazine > Diuron > Paraquat, while at 0.01µM: Diuron > Paraquat > Atrazine> Simazine. For the immobilised conditions, no 50% inhibition of cell number was observed, suggesting the cells were protected by alginate. In conclusion, immobilised cells are potential useful bio-indicator for herbicide or other pollutant that interfere with photosynthesis in water body. However, further research should be done to improve and simplify the method.